Маркетинговые коммуникации в интернет - Апатова, Н.В.; Перцев, А.Ю. (Культура народов Причерноморья, 2014)
Рассматриваются новые возможности организации маркетинга в компьютерной сети
Интернет с использованием средств коммуникаций, которые позволяют быстро находить целевую
группу для предложения товаров и услуг, повышать эффективность коммерческой деятельности за
счет увеличения продаж, удерживать клиентов и противостоять конкуренции. Розглядуються нові можливості організації маркетингу у комп’ютерної мережі Інтернет із
використанням засобів комунікацій, які дозволяють швидко знаходити цільову групу для пропозиції
товарів та послуг, підвисити ефективність комерційної діяльності за рахунок збільшення продажів,
утримання клієнтів та протидії конкурентів. Explores new possibilities marketing organization in a computer network using the Internet
communication tools that allow you to quickly find the target group for the supply of goods and services,
increase the efficiency of commercial activities due to increased sales, retain customers and to withstand
competition.
Unidirectional communication of traditional marketing, focused just on the delivery of the advertising message
to the target audience, transformed into the need to constantly maintain a dialogue and build long-term
relationships with each client.
Marketing on the Internet has an existing tool, which is based on the means of communication between economic
agents. These funds are especially mediated propagation speed communications, their vulnerability to
competition and susceptibility institutional environment. Internet Market requires continuous monitoring and
analysis of competitors, avoid purposeful misrepresentation. The subject of communication must constantly
manage target groups, to regulate e-mail messages and respond to consumer reviews. Internet creates huge
opportunities for market analysis, quick polls and study the behavior of consumers, thus increasing the efficiency
of business.